EXOTIC RED-BELLIED PACU, PIARACTUS BRACHYPOMUS (CUVIER, 1818) RECORDED FOR THE FIRST TIME FROM A TROPICAL RIVER WAINGANGA, MAHARASHTRA, INDIA - WANJARI, RINKESH N.; SHAH, TASADUQ H; TELVEKAR, PRASHANTA; BHAT, FAROOZA; ABUBAKAR, ADNAM; BHAT, BILALA; DARVE, SABINA I.; RAMTEKE, KARANKUMAR K.; DHANALAKSHMIM (Journal of the Inland Fisheries Society of India, 2025)
An exotic, red-bellied fish pacu also known as Roopchand or Pirapitinga, Piaractus brachypomus (Cuvier, 1818) (Characiformes: Serrasalmidae) is sold as a freshwater pomfret and possesses pomfret-like characteristics. P. brachypomus is a highly valued  ornamental and aquaculture fish species. In this study, P. brachypomus is reported for the first time from the Wainganga River at Kardha, Bhandara district, Maharashtra. The species was encountered near Kardha village (21 ° 082 52.25" N latitude and 79 ° 402 10.20" E longitude) of Bhandara district, eastern part of Maharashtra. In the present study, three specimens, ranging in length and weight from 300.51mm to 314.73mm and 305.62 to 346.12 g respectively, were caught using a gill net from the open waters of the river. The probable reasons for the catch may be accidental entry into the river or there may be an established viable population. This study aims to provide information on P. brachypomus, an aquarium ornamental fish species, collected in the open waters of the tropical Wainganga River.